Development of lemon flavored guava (Psidium Guajava Linnaeus) tea - Velasco, Pia Angela Avila; Galvez, Flor Crisanta F. (1999.)
An acceptable guava tea was developed and the process optimized by performing a series of experiments and sensory evaluation tests. The guava leaves, whose initial moisture content was 61.03%, were appropriately dried to a moisture content of about 3-5% by applying a range of 20-60 minutes drying time for the various drying temperature and blanching time combinations. A net weight of about 80 grams of freshly picked guava leaves'even drying, produced an average 20.9 grams of guava tea base. The 60°C drying temperature and 3 minutes blanching time combination was found to be the optimum as this combination produced dried guava leaves which yielded a guava tea beverage that was rated as the most acceptable by a total of 25 panelists in the sensory evaluation test which made use of 9-point hedonic scales. the leaves were i turn, flavored with the optimum level of lemon extract concentration which was deemed as the most acceptable on the basis of the mean panel scores for each attribute.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tea; Guava